Genetic polymorphism at Val80 (rs700518) of the CYP19A1 gene is associated with body composition changes in women on aromatase inhibitors for ER (+) breast cancer. Issue 8 (August 2015) - Napoli, Nicola; Rastelli, Antonella; Ma, Cynthia; Colleluori, Georgia; Vattikuti, Swapna; Armamento-Villareal, Reina
Abstract : Objective: Polymorphisms in the CYP19A1 (aromatase) gene influence disease-free survival and bone loss in patients taking aromatase inhibitors (AIs) for estrogen receptor-positive (ER+) breast cancers. Because AI use results in severe estrogen deficiency that may lead to changes in body composition, the aim of this study was to determine the effect of the rs700518 polymorphism in the CYP19A1 gene on the changes in body composition among postmenopausal women who were treated with AIs for ER+ breast cancer. Patients and methods: This was a 1-year prospective study of changes in body composition in postmenopausal women who were initiated on third-generation AIs for ER+ breast cancer. Body composition was measured by dual-energy absorptiometry at 6 and 12 months, serum estradiol by radioimmunoassay, and genotyping by a TaqMan single-nucleotide polymorphism allelic discrimination assay. Results: Eighty-two women could provide at least one follow-up body composition measurement. Women with the GG genotype for the rs700518 (G/A at Val80) developed a significant increase in truncal fat mass index ( P =0.03) and a significant decrease in fat-free mass index ( P =0.01) at 12 months relative to patients carrying the A allele (GA/AA). There was no significant difference in the changes in estradiol levels among the genotypes. Conclusion: Patients with the GG genotype for the rs700518 polymorphism in the CYP19A1 gene are at risk for significant loss of fat-free mass and increase in truncal fat with AI therapy. Whether there are associated metabolic abnormalities and whether changes would persist with long-term AI therapy need to be confirmed in a larger study with a longer duration of follow-up.